2014
DOI: 10.1186/1471-2458-14-728
|View full text |Cite
|
Sign up to set email alerts
|

Tools to support evidence-informed public health decision making

Abstract: BackgroundPublic health professionals are increasingly expected to engage in evidence-informed decision making to inform practice and policy decisions. Evidence-informed decision making involves the use of research evidence along with expertise, existing public health resources, knowledge about community health issues, the local context and community, and the political climate. The National Collaborating Centre for Methods and Tools has identified a seven step process for evidence-informed decision making. Too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 55 publications
1
118
0
5
Order By: Relevance
“…Although the Framework drew on literature available at its time of development (2012), subsequent work (e.g. Brown, 2012;Ettelt et al, 2013;Evans et al, 2013;Moat et al, 2013;Oliver et al, 2014;Panisset et al, 2012;Pitchforth et al, 2013;Yost et al, 2014) have largely confirmed previous reviews and the basis of the Framework.…”
Section: Discussionmentioning
confidence: 71%
“…Although the Framework drew on literature available at its time of development (2012), subsequent work (e.g. Brown, 2012;Ettelt et al, 2013;Evans et al, 2013;Moat et al, 2013;Oliver et al, 2014;Panisset et al, 2012;Pitchforth et al, 2013;Yost et al, 2014) have largely confirmed previous reviews and the basis of the Framework.…”
Section: Discussionmentioning
confidence: 71%
“…The concise definition proposed by Kohatsu puts a stronger focus on participatory decision making: “evidence-based public health is the process of integrating science-based interventions with community preferences to improve the health of populations” (p. 419) (116). Particularly in Canada and Australia, the term “evidence- informed decision making” is commonly used (5, 187), in part, to emphasize that public health decisions are not based only on research but particularly need to consider political and organizational factors (179). In a similar vein, Green has argued that we not only need a focus on evidence-based practice but also on practice-based evidence (80, 81).…”
Section: Why Evidence-based Public Health Mattersmentioning
confidence: 99%
“…Although nurses' decisions regarding adherence to clinical guidelines and whether to leave or remove IV devices have been investigated and reported in the literature (Cicolini et al, ; Jeffery & Pickler, ; Johansson, Pilhammar, Khalaf, & Willman, ; Johansson, Pilhammar, & Willman, ; Palese et al, ), nurses' decision‐making regarding administration set replacement has not been previously assessed. Understanding the knowledge and practical considerations underpinning clinical decision‐making is a vital component of laying the groundwork for knowledge translation (Yost et al, ).…”
Section: Introductionmentioning
confidence: 99%